Analysis of Gas Nitriding Characteristics under Different Cold Hardening and Nitriding Pressure Conditions for Low-Carbon Low-Alloy Steel - Zhou, Z A.; Fu, W.T.; Zhang, R.H.; Qi, J.J.; Jin, G.F.; Wang, Z.H.; Sun, S.H. (Проблемы прочности, 2018)
A new approach to quick preparation of a nitrided case for low-carbon low-alloy steels was proposed. It is based on cold hardening and pressurized gas nitriding. The microstructure, surface hardness, thickness, and corrosion resistance of the nitrided layer on low-carbon low-alloy steel (20CrMnTi) were investigated after the nitriding at 510°C for 5 h under different cold rolling reduction (0–60% CR) and nitriding pressure (1–5 atm). Предложен новый способ получения азотированного слоя на малоуглеродистых низколегированных сталях с использованием холодного деформирования и газового азотирования давлением. Изучены микроструктура, поверхностная твердость, толщина и коррозионная стойкость азотированного слоя на стали 20CrMnTi после азотирования при 510°С в течение 5 ч в различных условиях обжатия при холодной прокатке (0-60% СR) и давлении азотирования (1-5 атм).